Rapid moisture-conducting fiber as well as preparation method and application thereof
By adding coated modified functional particles to the spinning melt and performing high-multiple drafting, a rough surface structure is formed, which solves the problem of insufficient fiber moisture conduction performance, achieves rapid conduction of liquid and efficient moisture conduction performance of fabrics, and simplifies the process.
Patent Information
- Application Number
- CN202510194635.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-21
- Publication Date
- 2025-03-25
- Estimated Expiration
- 2045-02-21
AI Technical Summary
The existing fibers have insufficient moisture conduction performance, especially when sweating is large, and the traditional process is complex, which affects the comfort of wearing.
By adding 8~15% of the coated modified functional particles to the spinning melt and drafting 5.5~6.5 times during the spinning process, a large number of convex rough surface structures are formed, and the rapid conduction of the liquid is achieved by capillary action.
It significantly improves the wet conduction performance of the fiber, so that the fabric conducts annular radial conduction to the liquid in the three directions of X, Y, and Z, improves the conduction efficiency and spreading area, and the process is simple and easy to control.
Smart Images

Figure CN119685965A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of material science and textile technology, and relates to a fast moisture-conducting fiber and a preparation method and application thereof. Background Art
[0002] In the textile industry, the moisture conductivity of fibers is one of the important indicators for evaluating the comfort of fabrics. Traditional chemical fiber fabrics are mostly obtained by melt spinning, and their surfaces are usually smooth. The wettability and conductivity of water molecules on their surfaces are poor, which is not conducive to the rapid absorption and discharge of sweat. In order to improve the moisture conductivity of fibers, researchers have conducted a lot of exploration and practice.
[0003] A common method is to blend natural fibers with chemical synthetic fibers. For example, patent application CN118308830A discloses a processing technology for quick-drying antibacterial cotton fiber blended fabrics, in which cotton fibers mixed with heat-expandable microspheres and cotton fibers mixed with antibacterial aerogels are blended with polyester fibers, and hydrophilic groups are introduced through plasma treatment to adjust the hydrophilicity and hydrophobicity of the yarns. Patent application CN118345551A discloses a moisture-absorbing quick-drying fabric, which is woven by blending pure cotton fibers with hollow polyester fibers. This method uses the hydrophilicity of natural fibers to absorb moisture and the hydrophobicity of synthetic fibers to discharge moisture, but the absorption and discharge effects are limited and cannot meet the needs of situations with large amounts of sweat.
[0004] One method is to use a special weaving method to form a special fabric structure. For example, patent application CN118360722A discloses a warp-knitted double-sided fluff fabric with moisture absorption and quick-drying functions and a preparation method thereof. The fabric consists of 6 layers, and is woven from a first extension line layer and a first coil layer by a special-section fiber yarn, and a concave-convex structure is formed between the coil layers to achieve moisture absorption and quick-drying functions. Patent application CN118186671A discloses a knitted fabric based on modified polyamide fiber material and a preparation method thereof. The knitted fabric is obtained by circularly weaving mosquito-repellent modified fibers and polyurethane fibers according to a number of groups of circular weaving units, and a honeycomb mesh structure is formed on the fabric to achieve rapid perspiration and moisture absorption. However, this method has a complex weaving process and often requires a multi-layer structure, which will increase the thickness of the fabric. For sportswear or summer clothes, the fabric is too thick and heavy, affecting the wearing comfort.
[0005] Another method is to use chemical fiber modification and heterogeneous cross-section. For example, patent application CN118048708A discloses a moisture-absorbing and quick-drying polyester fiber and fabric, which adjusts the hydrophilicity and hydrophobicity of polyester by introducing hydrophilic polyether segments and hydrophobic alkyl segments into polyester, and then processes the modified polyester into heterogeneous fibers by melt spinning. Patent application CN118407153A discloses a method for preparing multi-grooved heterogeneous fibers and fabrics thereof, using alkali-soluble polyester COPET slices and nylon 6 slices as the skin layer and core layer respectively, and preparing heterogeneous two-component skin-core structured primary fibers by melt spinning, and finally completely dissolving part of COPET by alkali treatment to obtain heterogeneous multi-grooved nylon fibers. Patent application CN118581593A discloses a high-sweat absorption color spinning yarn and its preparation method, which uses polyester as raw material, introduces polyether segments and fluorine-containing segments into polyester molecular chains, and increases the fiber specific surface area by generating microcracks at the fluorine-containing segments during the stretching process to achieve moisture absorption and quick drying. Patent application CN118581731A discloses a method for preparing a novel synthetic fiber and its application, wherein acrylic staple fibers and organic amines are subjected to functional grafting reaction, and then the acrylic staple fibers and acidic solutions are subjected to transformation reaction to obtain novel synthetic fibers. The modification process in this method is complex and the conditions are harsh, and the effect is limited. Although the moisture conductivity of special-shaped cross-section fibers is better than that of ordinary fibers, the conduction direction is mainly along the fiber axis, and the conduction capacity along the Z direction in the fabric is poor. In addition, there is often a phenomenon of edges and grooves fitting each other between single fibers in the tow, which affects the conduction of liquid on the fiber surface.
[0006] In summary, the existing technology still has many deficiencies in improving the moisture conductivity of fibers. Therefore, it is of great significance to develop a fiber preparation method with excellent moisture conductivity, simple process and easy control. Summary of the invention
[0007] The purpose of the present invention is to solve the problems existing in the prior art and to provide a fast moisture-conducting fiber and a preparation method and application thereof.
[0008] To achieve the above object, the technical solution adopted by the present invention is as follows:
[0009] A method for preparing a fiber with rapid moisture conduction, comprising spinning a spinning melt containing 8-15wt% of coated modified functional particles, and performing a drafting process of 5.5-6.5 times during the spinning process, thereby obtaining the fiber with rapid moisture conduction;
[0010] The D50 particle size (i.e. median diameter or median particle size) of the coated modified functional particles is 50~900nm;
[0011] The coated modified functional particles include functional particles and oligomers coated on the surface of the functional particles through covalent bonds. The oligomers and the matrix of the spinning melt are only different in average polymerization degree, and the average polymerization degree of the oligomers is 20-60.
[0012] As the preferred technical solution:
[0013] In the method for preparing a fast moisture-conducting fiber as described above, the functional particles are silicon dioxide, titanium dioxide, zinc oxide, cuprous oxide or aluminum oxide, and the morphology can be spherical and amorphous nanoparticles; the thickness of the oligomers on the surface of the functional particles is 10-100 nm.
[0014] The method for preparing a fast moisture-conducting fiber as described above is a method for preparing coated modified functional particles: first, a coupling agent is used to organically modify the functional particles to obtain coupling agent-modified functional particles, and oligomers are prepared at the same time, and then the oligomers are mixed with the coupling agent-modified functional particles and reacted.
[0015] The method for preparing a fast moisture-conducting fiber as described above, wherein the coupling agent is one or more of γ-aminopropyl triethoxysilane, γ-(2,3-epoxypropoxy)propyl trimethoxysilane, γ-methacryloxypropyl trimethoxysilane, N-(β-aminoethyl)-γ-aminopropyl trimethoxy(ethyl)silane, n-octyl triethoxysilane, vinyl triethoxysilane, isopropyl triisostearate titanate, isopropoxy tri(dioctyl pyrophosphate acyloxy) titanate, tridecafluorooctyl trimethoxysilane, and perfluorodecyl trimethoxysilane; the mass of the coupling agent is 3-5% of the mass of the functional particles; the organic modification is completed in a high-speed blender at a speed of 2500-3000 r / min, a temperature of 80-100°C, and a time of 2-3h.
[0016] In the method for preparing a fast moisture-conducting fiber as described above, the oligomer is a polyester oligomer, the matrix of the spinning melt is polyester, and the preparation steps of the coated modified functional particles are as follows:
[0017] (a) using a coupling agent to organically modify the functional particles to obtain coupling agent-modified functional particles;
[0018] (b) adding the dibasic acid and diol into a reaction kettle, stirring and heating to 200-230°C, controlling the pressure of the reaction system to be 0.2-0.3MPa, adding a catalyst after reacting for 3-5h, controlling the temperature of the reaction system to gradually rise to 260-270°C, evacuating to a vacuum degree of less than 80Pa, reacting for 2-3h, cooling to 230°C, and obtaining an oligomer;
[0019] (c) adding the coupling agent modified functional particles to the reaction system of step (b), stirring at high speed to fully mix, keeping the temperature for reaction for 0.5 to 1 hour, continuously evacuating, discharging, cooling, pre-crushing, and airflow crushing to obtain coated modified functional particles;
[0020] The dibasic acid is terephthalic acid; the diol is one or more of ethylene glycol, propylene glycol and butanediol; and the catalyst is antimony ethylene glycol or tetrabutyl titanate.
[0021] In the method for preparing a fast moisture-conducting fiber as described above, the molar ratio of the dibasic acid to the diol is 1:0.9-0.95; the mass of the catalyst is 0.01-0.1% of the mass of the dibasic acid; and the mass ratio of the coupling agent-modified functional particles to the oligomer is 5-8:1.
[0022] In the method for preparing a fast moisture-conducting fiber as described above, the oligomer is a polyamide oligomer, the matrix of the spinning melt is polyamide, and the preparation steps of the coated modified functional particles are as follows:
[0023] (I) using a coupling agent to organically modify the functional particles to obtain coupling agent-modified functional particles;
[0024] (II) Add dibasic acid, diamine and deionized water into a reactor, replace the air in the reactor with nitrogen or inert gas (i.e., introduce 0.3-0.6MPa of nitrogen or inert gas into the reactor, open the exhaust valve to discharge, and repeat 3 times), react at 250°C and 1.3-1.8MPa for 3h, then reduce the pressure to 0.1MPa, add a catalyst, raise the temperature to 260°C, and turn on the vacuum pump to maintain the vacuum degree below 80Pa, react for 2-3h, then introduce nitrogen or inert gas to raise the pressure to 0.1MPa, and reduce the temperature to 220°C to obtain an oligomer;
[0025] (III) adding the coupling agent modified functional particles to the reaction system of step (II), stirring at high speed to fully mix, keeping the temperature for reaction for 0.5 to 1 hour, continuously evacuating, discharging, cooling, pre-crushing, and airflow crushing to obtain coated modified functional particles;
[0026] The dibasic acid is one or more of succinic acid, glutaric acid, adipic acid, pimelic acid, suberic acid, azelaic acid, and sebacic acid; the diamine is one or more of pentamethylenediamine and ethylenediamine; and the catalyst is tetrabutyl titanate.
[0027] In the method for preparing a fast moisture-conducting fiber as described above, the molar ratio of the dibasic acid to the diamine is 1:0.9~0.95; the molar ratio of deionized water to the dibasic acid is 0.3~0.4:1; the mass of the catalyst is 0.05~0.1% of the mass of the dibasic acid; and the mass ratio of the coupling agent-modified functional particles to the oligomer is 5~8:1.
[0028] As described above, a method for preparing a fast moisture-conducting fiber, the preparation process of the spinning melt is: first, resin A and the coated modified functional particles are melt-blended to obtain a masterbatch with a concentration of 50~65wt%, and then the masterbatch is melt-blended with resin B to obtain a spinning melt, wherein resin A and resin B are the same substance.
[0029] In the method for preparing a fast moisture-conducting fiber as described above, four pairs of drafting rollers are used for drafting; the temperature of the first pair of drafting rollers is 100~120°C, the temperature of the second pair of drafting rollers is 130~150°C, the temperature of the third pair of drafting rollers is 180~200°C, and the temperature of the fourth pair of drafting rollers is 200~240°C; the spinning speed of the first pair of drafting rollers is 400~500m / min, the spinning speed of the second pair of drafting rollers is 1200~1500m / min, the spinning speed of the third pair of drafting rollers is 2400~2600m / min, and the spinning speed of the fourth pair of drafting rollers is 2600~2800m / min.
[0030] In the preparation method of a fiber with rapid moisture conduction as described above, spinning is directly carried out according to the FDY process, or first spinning is carried out according to the POY process to obtain POY yarn, and then the POY yarn is subjected to alkali etching treatment, and then the POY yarn after alkali etching treatment is stretched. The alkali etching treatment is to soak the POY yarn in a NaOH aqueous solution with a temperature of 90-95°C and a concentration of 120-170g / L for 1-2 minutes, wash it with hot water at 60°C, and dry it at 120°C. The alkali etching treatment can remove part of the resin (i.e., polyester or polyamide) on the fiber surface, so that the coated modified functional particles are more prominent on the fiber surface, thereby further enhancing the moisture conduction performance of the fiber.
[0031] The present invention also provides a fast moisture-conducting fiber prepared by the method for preparing a fast moisture-conducting fiber as described in any of the above items, wherein the monofilament has a convex rough surface with one convexity every 0.5-2 μm, and the specification is 20-300D / 24-576F.
[0032] The present invention also provides a fast moisture-conducting yarn, which is spun from the fast moisture-conducting fiber as described above.
[0033] The present invention also provides a fast moisture-conducting fabric, which is woven from the fast moisture-conducting yarn as described above.
[0034] As the preferred technical solution:
[0035] The above-mentioned fast moisture-conducting fabric is a knitted fabric, the number of needles of the circular knitting machine is 40G, and the weight is 150~300g / m 2 Or, the fabric for rapid moisture conduction is a woven plain fabric with a warp density of 120-130 strands / 10cm, a weft density of 130-150 strands / 10cm, and a gram weight of 40-300g / m 2 Or, the fabric for fast moisture conduction is a woven twill fabric with a warp density of 120-190 strands / 10cm, a weft density of 140-150 strands / 10cm, and a gram weight of 60-300g / m 2The water absorption rate of the fast moisture-wicking fabric is ≥152%, the water droplet diffusion time is ≤1.9s, the wicking height is ≥112mm, and the drying rate is ≥0.45g / h, as tested according to the reference standard GB / T21655.1-2023.
[0036] Principle of the invention:
[0037] The present invention forms a large number of protruding rough structures on the fiber surface through a specific preparation process, which is similar to distributing a large number of dot arrays on the fiber surface, and forming a large number of tiny channels between the dot arrays. These structures can significantly enhance the capillary action of the fiber surface, thereby realizing rapid conduction of liquid;
[0038] First, the present invention adds a certain content (8-15wt%) of coated modified functional particles with a specific particle size (D50 particle size of 50-900nm) to the spinning melt to ensure the packing density of the inorganic particles in the fiber, while avoiding the decrease in the matrix strength of the spinning melt due to excessively high content, thereby affecting the spinnability of the fiber; the coated modified functional particles are composed of functional particles and oligomers coated on the surface thereof by covalent bonds, wherein the functional particles can give the fiber specific functionality (such as anti-transmission, anti-ultraviolet, antibacterial, etc.), and the oligomers are different from the matrix of the spinning melt only in the average polymerization degree, thereby ensuring the good compatibility of the coated modified functional particles with the spinning melt;
[0039] If the amount of coated modified functional particles added is too high, the spinnability of the fiber will decrease, making the fiber easy to break during the subsequent drawing process; if the amount of coated modified functional particles added is too low, the distribution of the coated modified functional particles on the fiber surface will be relatively insufficient, affecting the formation of protrusions on the fiber surface, resulting in weakened fiber functionality;
[0040] The D50 particle size of the coated modified functional particles is controlled within the range of 50-900 nm to ensure uniform distribution of the particles in the fiber; if the particle size of the coated modified functional particles is too large, the spinnability of the fiber will be affected, causing the fiber to be easily broken during the subsequent drawing process; if the particle size of the coated modified functional particles is too small, the roughness formed on the fiber surface is low, which will weaken the capillary effect of the fiber surface and further affect the moisture conductivity of the fiber;
[0041] Secondly, the present invention performs a high multiple drafting (5.5-6.5 times) during the spinning process, which not only makes the fiber thinner, but also makes the coated modified functional particles squeeze each other and expose on the fiber surface during the fiber drafting process, forming a large number of protrusion structures. These protrusion structures are similar to dot arrays, and a large number of tiny channels (i.e., grooves) are formed between them. These channels promote the rapid conduction of liquid on the fiber surface through capillary action. This conduction effect is not limited to the axial direction of the fiber, but can also be carried out in the radial direction of the fiber (such as Figure 1As shown in the figure, the liquid can be quickly and omnidirectionally conducted on the fiber surface. If the drafting is excessive, the roughness of the fiber surface can be further increased, but the broken yarn rate will increase and the processing cannot be performed. If the drafting is insufficient, the fiber will not be fine enough, the protrusion structure will not be formed enough, and the number and size of the micro-channels will be reduced, which will limit the rapid conduction of the liquid on the fiber surface and weaken the moisture conduction performance of the fiber.
[0042] The fast moisture-conducting fibers in the present invention can be ordinary circular cross-section fibers or special-shaped cross-section fibers. The yarns spun from these fibers have a large number of capillary-like channels (such as Figure 2 As shown in Figure 2, these channels not only promote the conduction of liquid in the yarn, but also enable the fabric made of yarn to conduct liquid in a circular radial manner in the X, Y, and Z directions, greatly improving the conduction efficiency and spreading area.
[0043] Beneficial effects:
[0044] (1) The present invention adds specific coated modified functional particles to the spinning melt and controls the content, and performs a specific multiple of drafting, so that a rough surface structure with a large number of protrusions is formed on the fiber surface, which is similar to a dot array, and grooves are formed between the protrusions. Capillary action is used to promote the rapid conduction and spreading of liquid on the surface of a single fiber, thereby improving the moisture conductivity of the fiber.
[0045] (2) For the yarn, since the raised surface structures of the monofilaments support each other to form a large number of capillary-like channels, the fabric made of the yarn of the present invention can conduct liquid in a circular radial manner along the three directions of X, Y, and Z, thereby improving the conduction efficiency and spreading area, and having a good quick-drying effect on volatile liquids such as water and sweat.
[0046] (3) Compared with the prior art, the present invention avoids the problems of limited absorption and discharge effects of blending natural fibers with chemical synthetic fibers, complex special weaving processes, increased fabric thickness affecting wearing comfort, and complex chemical fiber modification processes with harsh conditions and limited effects. At the same time, the process is simple and easy to control. BRIEF DESCRIPTION OF THE DRAWINGS
[0047] Figure 1 Schematic diagram of the protrusion structure and tiny channels on the fiber surface;
[0048] Figure 2 Schematic diagram of the capillary-like channels inside the yarn. DETAILED DESCRIPTION
[0049] The present invention will be further described below in conjunction with specific embodiments. It should be understood that these embodiments are only used to illustrate the present invention and are not intended to limit the scope of the present invention. In addition, it should be understood that after reading the content taught by the present invention, those skilled in the art can make various changes or modifications to the present invention, and these equivalent forms fall within the scope limited by the appended claims of the application equally.
[0050] The following are the test methods for the relevant performance indicators in each embodiment and comparative example:
[0051] Average degree of polymerization: tested by gel permeation chromatography (GPC).
[0052] Water absorption: Tested according to 8.1 water absorption test method in GB / T 21655.1-2023.
[0053] Water droplet diffusion time: Tested according to 8.2 Water droplet diffusion time in GB / T 21655.1-2023.
[0054] Drying rate: Tested according to 8.3 Drying rate in GB / T 21655.1-2023.
[0055] Wicking height: Tested according to 8.4 Wicking height in GB / T 21655.1-2023.
[0056] Example A1
[0057] A method for preparing a fabric with rapid moisture conduction, the specific steps are as follows:
[0058] (1) Preparation of raw materials;
[0059] Coupling agent: γ-aminopropyltriethoxysilane;
[0060] Functional particles: silicon dioxide;
[0061] Dibasic acid: terephthalic acid;
[0062] Diol: ethylene glycol;
[0063] Catalyst: Antimony glycol;
[0064] Resin A and Resin B: both are PET with an average degree of polymerization of 600;
[0065] NaOH aqueous solution: temperature 90°C, concentration 130g / L;
[0066] (2) Preparation of coated modified functional particles;
[0067] (2.1) In a high-speed blender, at a speed of 3000 r / min and a temperature of 80° C., the functional particles are subjected to organic modification using a coupling agent for 2.5 hours to obtain coupling agent-modified functional particles; wherein the mass of the coupling agent is 5% of the mass of the functional particles;
[0068] (2.2) Add the dibasic acid and diol into a reaction kettle, stir and heat to 200°C, control the pressure of the reaction system to be 0.2MPa, add the catalyst after reacting for 3.5h, control the temperature of the reaction system to gradually rise to 265°C, evacuate to 63Pa, react for 2.5h and cool to 230°C to obtain a polyester oligomer with an average degree of polymerization of 48; wherein the molar ratio of the dibasic acid to the diol is 1:0.9; the mass of the catalyst is 0.04% of the mass of the dibasic acid;
[0069] (2.3) Adding coupling agent modified functional particles to the reaction system of step (2.2), stirring to fully mix, keeping the temperature for reaction for 0.8h, continuously evacuating, discharging, cooling, pre-crushing, air flow crushing, and obtaining coated modified functional particles; wherein the mass ratio of coupling agent modified functional particles to polyester oligomer is 6:1;
[0070] The prepared coated modified functional particles consist of functional particles and polyester oligomers coated on the surface thereof, and the functional particles and the polyester oligomers are covalently bonded via a coupling agent; the D50 particle size of the coated modified functional particles is 200 nm, and the thickness of the polyester oligomers on the surface of the functional particles is 80 nm;
[0071] (3) preparing a spinning melt;
[0072] First, resin A and coated modified functional particles are melt-blended to obtain a masterbatch with a concentration of 65wt%, and then the masterbatch is melt-blended with resin B to obtain a spinning melt;
[0073] In the spinning melt, the content of the coated modified functional particles is 8wt%;
[0074] (4) Preparation of fibers that conduct moisture quickly;
[0075] First, the spinning melt is spun according to the POY process to obtain POY fibers, and then the POY fibers are soaked in a NaOH aqueous solution for 1.5 minutes, washed, and dried, and then the POY fibers are drawn using four pairs of drawing rollers to obtain fibers with rapid moisture conduction;
[0076] Among them, the temperature of the first pair of drafting rollers is 100°C, the temperature of the second pair of drafting rollers is 130°C, the temperature of the third pair of drafting rollers is 180°C, and the temperature of the fourth pair of drafting rollers is 200°C; the spinning speed of the first pair of drafting rollers is 400m / min, the spinning speed of the second pair of drafting rollers is 1200m / min, the spinning speed of the third pair of drafting rollers is 2400m / min, and the spinning speed of the fourth pair of drafting rollers is 2600m / min;
[0077] The specification of the obtained fast moisture-conducting fiber is 20D / 24F; the monofilament of the fast moisture-conducting fiber has a convex rough surface, with one convexity every 0.5-2 μm, and the average distance between adjacent convexities is 1.6 μm;
[0078] (5) Preparation of fabrics with rapid moisture conduction;
[0079] Firstly, the fast moisture-conducting fiber is spun to obtain the fast moisture-conducting yarn, and then the fast moisture-conducting yarn is woven into the fast moisture-conducting fabric.
[0080] The final fast moisture-conducting fabric is a woven plain fabric with a warp density of 120 strands / 10cm, a weft density of 130 strands / 10cm, and a gram weight of 40g / m 2 The water absorption rate of the fast-wicking fabric is 172%, the water droplet diffusion time is 1.3s, the wicking height is 123mm, and the drying rate is 0.58g / h.
[0081] Comparative Example 1
[0082] A method for preparing a fabric is basically the same as that of Example A1, except that the content of the coated modified functional particles in the spinning melt obtained in step (3) is 6 wt %.
[0083] The final fabric had a water absorption of 94%, a water droplet diffusion time of 3.6 s, a wicking height of 83 mm, and a drying rate of 0.24 g / h.
[0084] Compared with Example A1, the moisture conductivity of the fabric in Comparative Example 1 is significantly reduced. This is because the amount of coated modified functional particles added to the spinning melt in Comparative Example 1 is too low, and the distribution amount of coated modified functional particles on the fiber surface is relatively insufficient, which affects the formation of protrusions on the fiber surface, weakens the capillary effect on the fiber surface, and further affects the moisture conductivity of the fiber.
[0085] Comparative Example 2
[0086] A method for preparing a fabric is basically the same as that of Example A1, except that in step (2.3), the process parameters of pre-crushing and airflow crushing are adjusted so that the D50 particle size of the coated modified functional particles is 40 nm.
[0087] The final fabric had a water absorption of 82%, a water droplet diffusion time of 4.5 s, a wicking height of 87 mm, and a drying rate of 0.21 g / h.
[0088] Compared with Example A1, the moisture conductivity of the fabric in Comparative Example 2 is significantly reduced. This is because the particle size of the coated modified functional particles in Comparative Example 2 is too small, and the particles are difficult to squeeze out of the resin during the stretching process, and no obvious convex structure can be formed on the fiber surface. The roughness of the fiber surface is low, resulting in a weakened capillary effect on the fiber surface, which in turn affects the moisture conductivity of the fiber.
[0089] Comparative Example 3
[0090] A method for preparing a fabric is substantially the same as that of Example A1, except that in step (4), the spinning speed of the first pair of drafting rollers is 400 m / min, the spinning speed of the second pair of drafting rollers is 800 m / min, the spinning speed of the third pair of drafting rollers is 1500 m / min, and the spinning speed of the fourth pair of drafting rollers is 1800 m / min.
[0091] The final fabric had a water absorption of 88%, a water droplet diffusion time of 3.5 s, a wicking height of 90 mm, and a drying rate of 0.26 g / h.
[0092] Compared with Example A1, the moisture conductivity of the fabric in Comparative Example 3 is significantly reduced. This is because the drafting of Comparative Example 3 is insufficient, the fiber refinement is not enough, the protrusion structure is insufficiently formed, and the number and size of tiny channels are reduced, which will limit the rapid conduction of liquid on the fiber surface and weaken the moisture conductivity of the fiber.
[0093] Example A2
[0094] A method for preparing a fabric with rapid moisture conduction is basically the same as that in Example A1, except that the specific process of step (4) is: spinning the spinning melt directly according to the FDY process, and using four pairs of drafting rollers for drafting during the spinning process (the relevant process parameters are the same as those in Example A1) to obtain a fiber with rapid moisture conduction.
[0095] The final fast moisture-wicking fabric had a water absorption rate of 154%, a water droplet diffusion time of 1.9 s, a wicking height of 112 mm, and a drying rate of 0.45 g / h.
[0096] Compared with Example A2, Example A1 has a better moisture conduction performance of the fast moisture conduction fabric. This is because the alkaline etching treatment can remove part of the resin (i.e., polyester) on the fiber surface, allowing the coated modified functional particles to protrude more from the fiber surface, forming a denser moisture conduction channel, thereby further enhancing the moisture conduction performance of the fiber.
[0097] Example A3
[0098] A method for preparing a fabric with rapid moisture conduction, the specific steps are as follows:
[0099] (1) Preparation of raw materials;
[0100] Coupling agent: γ-(2,3-epoxypropoxy)propyltrimethoxysilane;
[0101] Functional particles: titanium dioxide;
[0102] Dibasic acid: terephthalic acid;
[0103] Diol: Propylene glycol;
[0104] Catalyst: Antimony glycol;
[0105] Resin A and Resin B: both are PET with an average degree of polymerization of 720;
[0106] NaOH aqueous solution: temperature 95°C, concentration 100g / L;
[0107] (2) Preparation of coated modified functional particles;
[0108] (2.1) In a high-speed blender, at a speed of 2800 r / min and a temperature of 100° C., the functional particles are subjected to organic modification using a coupling agent for 2.8 hours to obtain coupling agent-modified functional particles; wherein the mass of the coupling agent is 3% of the mass of the functional particles;
[0109] (2.2) Add the dibasic acid and diol into a reaction kettle, stir and heat to 210°C, control the pressure of the reaction system to be 0.23MPa, add the catalyst after reacting for 3h, control the temperature of the reaction system to gradually rise to 268°C, evacuate to 68Pa, react for 2h and cool to 230°C to obtain a polyester oligomer with an average degree of polymerization of 40; wherein the molar ratio of the dibasic acid to the diol is 1:0.9; the mass of the catalyst is 0.01% of the mass of the dibasic acid;
[0110] (2.3) adding coupling agent modified functional particles to the reaction system of step (2.2), stirring to fully mix, keeping the temperature for reaction for 1 hour, continuously evacuating, discharging, cooling, pre-crushing, air flow crushing, and obtaining coated modified functional particles; wherein the mass ratio of coupling agent modified functional particles to polyester oligomer is 8:1;
[0111] The prepared coated modified functional particles consist of functional particles and polyester oligomers coated on the surface thereof, and the functional particles and the polyester oligomers are covalently bonded via a coupling agent; the D50 particle size of the coated modified functional particles is 900 nm, and the thickness of the polyester oligomers on the surface of the functional particles is 10 nm;
[0112] (3) preparing a spinning melt;
[0113] First, the resin A and the coated modified functional particles are melt-blended to obtain a masterbatch with a concentration of 50wt%, and then the masterbatch is melt-blended with the resin B to obtain a spinning melt;
[0114] In the spinning melt, the content of the coated modified functional particles is 15wt%;
[0115] (4) Preparation of fibers that conduct moisture quickly;
[0116] First, the spinning melt is spun according to the POY process to obtain POY fibers, and then the POY fibers are soaked in a NaOH aqueous solution for 2 minutes, washed, and dried, and then the POY fibers are drafted by four pairs of drafting rollers to obtain fibers with rapid moisture conduction;
[0117] Among them, the temperature of the first pair of drafting rollers is 120°C, the temperature of the second pair of drafting rollers is 150°C, the temperature of the third pair of drafting rollers is 200°C, and the temperature of the fourth pair of drafting rollers is 240°C; the spinning speed of the first pair of drafting rollers is 430m / min, the spinning speed of the second pair of drafting rollers is 1300m / min, the spinning speed of the third pair of drafting rollers is 2500m / min, and the spinning speed of the fourth pair of drafting rollers is 2800m / min;
[0118] The specification of the obtained fast moisture-conducting fiber is 75D / 36F; the monofilament of the fast moisture-conducting fiber has a convex rough surface, with one convexity every 0.5-2 μm, and the average distance between adjacent convexities is 0.6 μm;
[0119] (5) Preparation of fabrics with rapid moisture conduction;
[0120] Firstly, the fast moisture-conducting fiber is spun to obtain the fast moisture-conducting yarn, and then the fast moisture-conducting yarn is woven into the fast moisture-conducting fabric.
[0121] The final fast moisture-wicking fabric is a woven twill fabric with a warp density of 120 strands / 10cm, a weft density of 140 strands / 10cm, and a gram weight of 60g / m 2 The water absorption rate of the fast-wicking fabric is 163%, the water droplet diffusion time is 1.6s, the wicking height is 117mm, and the drying rate is 0.49g / h.
[0122] Example A4
[0123] A method for preparing a fabric with rapid moisture conduction, the specific steps are as follows:
[0124] (1) Preparation of raw materials;
[0125] Coupling agent: N-(β-aminoethyl)-γ-aminopropyltrimethyl(ethyl)oxysilane;
[0126] Functional particles: zinc oxide;
[0127] Dibasic acid: terephthalic acid;
[0128] Diol: a mixture of ethylene glycol and propylene glycol in a molar ratio of 1:1;
[0129] Catalyst: tetrabutyl titanate;
[0130] Resin A and Resin B: both are PET with an average degree of polymerization of 600;
[0131] NaOH aqueous solution: temperature 93°C, concentration 120g / L;
[0132] (2) Preparation of coated modified functional particles;
[0133] (2.1) In a high-speed blender, at a speed of 3000 r / min and a temperature of 100° C., the functional particles are subjected to organic modification using a coupling agent for 2 h to obtain coupling agent-modified functional particles; wherein the mass of the coupling agent is 3.5% of the mass of the functional particles;
[0134] (2.2) Add the dibasic acid and diol into a reaction kettle, stir and heat to 230°C, control the pressure of the reaction system to be 0.3MPa, add the catalyst after reacting for 5h, control the temperature of the reaction system to gradually rise to 270°C, evacuate to 60Pa, react for 3h and cool to 230°C to obtain a polyester oligomer with an average degree of polymerization of 53; wherein the molar ratio of the dibasic acid to the diol is 1:0.92; the mass of the catalyst is 0.1% of the mass of the dibasic acid;
[0135] (2.3) adding coupling agent modified functional particles to the reaction system of step (2.2), stirring to fully mix, keeping the temperature for reaction for 1 hour, continuously evacuating, discharging, cooling, pre-crushing, air flow crushing, and obtaining coated modified functional particles; wherein the mass ratio of coupling agent modified functional particles to polyester oligomer is 7:1;
[0136] The prepared coated modified functional particles consist of functional particles and polyester oligomers coated on the surface thereof, and the functional particles and the polyester oligomers are covalently bonded via a coupling agent; the D50 particle size of the coated modified functional particles is 400 nm, and the thickness of the polyester oligomers on the surface of the functional particles is 30 nm;
[0137] (3) preparing a spinning melt;
[0138] First, resin A and coated modified functional particles are melt-blended to obtain a masterbatch with a concentration of 60wt%, and then the masterbatch is melt-blended with resin B to obtain a spinning melt;
[0139] In the spinning melt, the content of the coated modified functional particles is 10wt%;
[0140] (4) Preparation of fibers that conduct moisture quickly;
[0141] First, the spinning melt is spun according to the POY process to obtain POY fibers, and then the POY fibers are soaked in a NaOH aqueous solution for 1.5 minutes, washed, and dried, and then the POY fibers are drawn using four pairs of drawing rollers to obtain fibers with rapid moisture conduction;
[0142] Among them, the temperature of the first pair of drafting rollers is 105°C, the temperature of the second pair of drafting rollers is 135°C, the temperature of the third pair of drafting rollers is 190°C, and the temperature of the fourth pair of drafting rollers is 220°C; the spinning speed of the first pair of drafting rollers is 450m / min, the spinning speed of the second pair of drafting rollers is 1200m / min, the spinning speed of the third pair of drafting rollers is 2400m / min, and the spinning speed of the fourth pair of drafting rollers is 2650m / min;
[0143] The specification of the obtained fast moisture-conducting fiber is 300D / 576F; the monofilament of the fast moisture-conducting fiber has a convex rough surface, with one convexity every 0.5-2 μm, and the average distance between adjacent convexities is 1 μm;
[0144] (5) Preparation of fabrics with rapid moisture conduction;
[0145] Firstly, the fast moisture-conducting fiber is spun to obtain the fast moisture-conducting yarn, and then the fast moisture-conducting yarn is woven into the fast moisture-conducting fabric.
[0146] The final fast moisture-conducting fabric is a woven twill fabric with a warp density of 190 strands / 10cm, a weft density of 150 strands / 10cm, and a gram weight of 300g / m 2 The water absorption rate of the fast-wicking fabric is 178%, the water droplet diffusion time is 1s, the wicking height is 125mm, and the drying rate is 0.63g / h.
[0147] Example A5
[0148] A method for preparing a fabric with rapid moisture conduction, the specific steps are as follows:
[0149] (1) Preparation of raw materials;
[0150] Coupling agent: isopropyl triisostearate titanate;
[0151] Functional particles: cuprous oxide;
[0152] Dibasic acid: terephthalic acid;
[0153] Diol: Butanediol;
[0154] Catalyst: tetrabutyl titanate;
[0155] Resin A and Resin B: both are PET with an average degree of polymerization of 720;
[0156] NaOH aqueous solution: temperature 95°C, concentration 150g / L;
[0157] (2) Preparation of coated modified functional particles;
[0158] (2.1) In a high-speed blender, at a speed of 2500 r / min and a temperature of 90°C, the functional particles are subjected to organic modification using a coupling agent for 3 hours to obtain coupling agent-modified functional particles; wherein the mass of the coupling agent is 4.5% of the mass of the functional particles;
[0159] (2.2) Add the dibasic acid and diol into a reaction kettle, stir and heat to 200°C, control the pressure of the reaction system to be 0.28MPa, add the catalyst after reacting for 4 hours, control the temperature of the reaction system to gradually rise to 260°C, evacuate to 72Pa, react for 2.5 hours and cool to 230°C to obtain a polyester oligomer with an average degree of polymerization of 60; wherein the molar ratio of the dibasic acid to the diol is 1:0.95; the mass of the catalyst is 0.08% of the mass of the dibasic acid;
[0160] (2.3) Adding coupling agent modified functional particles to the reaction system of step (2.2), stirring to fully mix, keeping the temperature for reaction for 0.5h, continuously evacuating, discharging, cooling, pre-crushing, air flow crushing, and obtaining coated modified functional particles; wherein the mass ratio of coupling agent modified functional particles to polyester oligomer is 5:1;
[0161] The prepared coated modified functional particles consist of functional particles and polyester oligomers coated on the surface thereof, and the functional particles and the polyester oligomers are covalently bonded via a coupling agent; the D50 particle size of the coated modified functional particles is 50 nm, and the thickness of the polyester oligomers on the surface of the functional particles is 100 nm;
[0162] (3) preparing a spinning melt;
[0163] First, resin A and coated modified functional particles are melt-blended to obtain a masterbatch with a concentration of 65wt%, and then the masterbatch is melt-blended with resin B to obtain a spinning melt;
[0164] In the spinning melt, the content of the coated modified functional particles is 8wt%;
[0165] (4) Preparation of fibers that conduct moisture quickly;
[0166] First, the spinning melt is spun according to the POY process to obtain POY fibers, and then the POY fibers are soaked in a NaOH aqueous solution for 1 minute, washed, and dried, and then the POY fibers are drawn using four pairs of drawing rollers to obtain fibers with rapid moisture conduction;
[0167] Among them, the temperature of the first pair of drafting rollers is 110°C, the temperature of the second pair of drafting rollers is 145°C, the temperature of the third pair of drafting rollers is 195°C, and the temperature of the fourth pair of drafting rollers is 235°C; the spinning speed of the first pair of drafting rollers is 500m / min, the spinning speed of the second pair of drafting rollers is 1500m / min, the spinning speed of the third pair of drafting rollers is 2600m / min, and the spinning speed of the fourth pair of drafting rollers is 2800m / min;
[0168] The specification of the obtained fast moisture-conducting fiber is 150D / 72F; the monofilament of the fast moisture-conducting fiber has a convex rough surface, with one convexity every 0.5-2 μm, and the average distance between adjacent convexities is 1.8 μm;
[0169] (5) Preparation of fabrics with rapid moisture conduction;
[0170] Firstly, the fast moisture-conducting fiber is spun to obtain the fast moisture-conducting yarn, and then the fast moisture-conducting yarn is woven into the fast moisture-conducting fabric.
[0171] The final fast moisture-wicking fabric is a knitted fabric with a circular knitting machine needle count of 40G and a gram weight of 200g / m 2 The water absorption rate of the fast-wicking fabric is 161%, the water droplet diffusion time is 1.4s, the wicking height is 118mm, and the drying rate is 0.52g / h.
[0172] Example B1
[0173] A method for preparing a fabric with rapid moisture conduction, the specific steps are as follows:
[0174] (1) Preparation of raw materials;
[0175] Coupling agent: γ-aminopropyltriethoxysilane;
[0176] Functional particles: titanium dioxide;
[0177] Dibasic acid: succinic acid;
[0178] Diamine: a mixture of pentamethylenediamine and ethylenediamine in a molar ratio of 1:1;
[0179] Deionized water;
[0180] Catalyst: tetrabutyl titanate;
[0181] Resin A and Resin B: both are polyamides with an average degree of polymerization of 200;
[0182] NaOH aqueous solution: temperature 90°C, concentration 150g / L;
[0183] (2) Preparation of coated modified functional particles;
[0184] (2.1) In a high-speed blender, at a speed of 3000 r / min and a temperature of 80° C., the functional particles are subjected to organic modification using a coupling agent for 2.5 hours to obtain coupling agent-modified functional particles; wherein the mass of the coupling agent is 5% of the mass of the functional particles;
[0185] (2.2) Add dibasic acid, diamine and deionized water into a reactor, replace the air in the reactor with nitrogen or inert gas (i.e., introduce 0.5 MPa of nitrogen or inert gas into the reactor, open the exhaust valve to discharge, and repeat 3 times), react at 250°C and 1.5 MPa for 3 hours, then reduce the pressure to 0.1 MPa, add catalyst, raise the temperature to 260°C, turn on the vacuum pump, maintain the vacuum degree at 68 Pa, react for 2 hours, then raise the pressure to 0.1 MPa, and reduce the temperature to 220°C to obtain a polyamide oligomer with an average degree of polymerization of 20; wherein the molar ratio of dibasic acid to diamine is 1:0.9, the molar ratio of deionized water to dibasic acid is 0.3:1, and the mass of the catalyst is 0.08% of the mass of the dibasic acid;
[0186] (2.3) Adding coupling agent modified functional particles to the reaction system of step (2.2), stirring to fully mix, keeping the temperature for reaction for 0.5h, continuously evacuating, discharging, cooling, pre-crushing, air flow crushing, and obtaining coated modified functional particles; wherein the mass ratio of coupling agent modified functional particles to polyester oligomer is 5:1;
[0187] The prepared coated modified functional particles consist of functional particles and polyamide oligomers coated on the surface thereof, and the functional particles and the polyamide oligomers are covalently bonded via a coupling agent; the D50 particle size of the coated modified functional particles is 900 nm, and the thickness of the polyamide oligomers on the surface of the functional particles is 30 nm;
[0188] (3) preparing a spinning melt;
[0189] First, the resin A and the coated modified functional particles are melt-blended to obtain a masterbatch with a concentration of 50wt%, and then the masterbatch is melt-blended with the resin B to obtain a spinning melt;
[0190] In the spinning melt, the content of the coated modified functional particles is 8wt%;
[0191] (4) Preparation of fibers that conduct moisture quickly;
[0192] First, the spinning melt is spun according to the POY process to obtain POY fibers, and then the POY fibers are soaked in a NaOH aqueous solution for 2 minutes, washed, and dried, and then the POY fibers are drafted by four pairs of drafting rollers to obtain fibers with rapid moisture conduction;
[0193] Among them, the temperature of the first pair of drafting rollers is 120°C, the temperature of the second pair of drafting rollers is 150°C, the temperature of the third pair of drafting rollers is 200°C, and the temperature of the fourth pair of drafting rollers is 240°C; the spinning speed of the first pair of drafting rollers is 430m / min, the spinning speed of the second pair of drafting rollers is 1250m / min, the spinning speed of the third pair of drafting rollers is 2600m / min, and the spinning speed of the fourth pair of drafting rollers is 2800m / min;
[0194] The specification of the obtained fast moisture-conducting fiber is 300D / 576F; the monofilament of the fast moisture-conducting fiber has a convex rough surface, with one convexity every 0.5-2 μm, and the average distance between adjacent convexities is 0.6 μm;
[0195] (5) Preparation of fabrics with rapid moisture conduction;
[0196] Firstly, the fast moisture-conducting fiber is spun to obtain the fast moisture-conducting yarn, and then the fast moisture-conducting yarn is woven into the fast moisture-conducting fabric.
[0197] The final fast moisture-conducting fabric is a woven plain fabric with a warp density of 130 strands / 10cm, a weft density of 150 strands / 10cm, and a gram weight of 300g / m 2 The water absorption rate of the fast-wicking fabric is 180%, the water droplet diffusion time is 1s, the wicking height is 129mm, and the drying rate is 0.68g / h.
[0198] Example B2
[0199] A method for preparing a fabric with rapid moisture conduction is basically the same as that in Example B1, except that the specific process of step (4) is: spinning the spinning melt directly according to the FDY process, and using four pairs of drafting rollers for drafting during the spinning process (the relevant process parameters are the same as those in Example B1) to obtain a fiber with rapid moisture conduction.
[0200] The final fast moisture-wicking fabric had a water absorption rate of 152%, a water droplet diffusion time of 1.8 s, a wicking height of 112 mm, and a drying rate of 0.46 g / h.
[0201] Compared with Example B2, Example B1 has a better moisture conduction performance of the fast moisture conduction fabric. This is because the alkali etching treatment can remove part of the resin (i.e., polyamide) on the fiber surface, allowing the coated modified functional particles to protrude more from the fiber surface, forming a denser moisture conduction channel, thereby further enhancing the moisture conduction performance of the fiber.
[0202] Example B3
[0203] A method for preparing a fabric with rapid moisture conduction, the specific steps are as follows:
[0204] (1) Preparation of raw materials;
[0205] Coupling agent: γ-(2,3-epoxypropoxy)propyltrimethoxysilane;
[0206] Functional particles: cuprous oxide;
[0207] Dibasic acid: adipic acid;
[0208] Diamine: pentamethylenediamine;
[0209] Deionized water;
[0210] Catalyst: tetrabutyl titanate;
[0211] Resin A and Resin B: both are polyamides with an average degree of polymerization of 150;
[0212] NaOH aqueous solution: temperature 95°C, concentration 120g / L;
[0213] (2) Preparation of coated modified functional particles;
[0214] (2.1) In a high-speed blender, at a speed of 2800 r / min and a temperature of 100° C., the functional particles are subjected to organic modification using a coupling agent for 2.8 hours to obtain coupling agent-modified functional particles; wherein the mass of the coupling agent is 3% of the mass of the functional particles;
[0215] (2.2) Add dibasic acid, diamine and deionized water into a reactor, replace the air in the reactor with nitrogen or inert gas (i.e., introduce 0.3 MPa of nitrogen or inert gas into the reactor, open the exhaust valve to discharge, and repeat 3 times), react at 250°C and 1.3 MPa for 3 hours, then reduce the pressure to 0.1 MPa, add catalyst, raise the temperature to 260°C, turn on the vacuum pump, maintain the vacuum degree at 65 Pa, react for 2.5 hours, then raise the pressure to 0.1 MPa, and reduce the temperature to 220°C to obtain a polyamide oligomer with an average degree of polymerization of 26; wherein the molar ratio of dibasic acid to diamine is 1:0.92, the molar ratio of deionized water to dibasic acid is 0.33:1, and the mass of the catalyst is 0.05% of the mass of the dibasic acid;
[0216] (2.3) Adding coupling agent modified functional particles to the reaction system of step (2.2), stirring to fully mix, keeping the temperature for reaction for 0.8h, continuously evacuating, discharging, cooling, pre-crushing, air flow crushing, and obtaining coated modified functional particles; wherein the mass ratio of coupling agent modified functional particles to polyester oligomer is 8:1;
[0217] The prepared coated modified functional particles consist of functional particles and polyamide oligomers coated on the surface thereof, and the functional particles and the polyamide oligomers are covalently bonded via a coupling agent; the D50 particle size of the coated modified functional particles is 50 nm, and the thickness of the polyamide oligomers on the surface of the functional particles is 10 nm;
[0218] (3) preparing a spinning melt;
[0219] First, resin A and coated modified functional particles are melt-blended to obtain a masterbatch with a concentration of 65wt%, and then the masterbatch is melt-blended with resin B to obtain a spinning melt;
[0220] In the spinning melt, the content of the coated modified functional particles is 8wt%;
[0221] (4) Preparation of fibers that conduct moisture quickly;
[0222] First, the spinning melt is spun according to the POY process to obtain POY fibers, and then the POY fibers are soaked in a NaOH aqueous solution for 1 minute, washed, and dried, and then the POY fibers are drawn using four pairs of drawing rollers to obtain fibers with rapid moisture conduction;
[0223] Among them, the temperature of the first pair of drafting rollers is 100°C, the temperature of the second pair of drafting rollers is 130°C, the temperature of the third pair of drafting rollers is 180°C, and the temperature of the fourth pair of drafting rollers is 200°C; the spinning speed of the first pair of drafting rollers is 400m / min, the spinning speed of the second pair of drafting rollers is 1200m / min, the spinning speed of the third pair of drafting rollers is 2500m / min, and the spinning speed of the fourth pair of drafting rollers is 2600m / min;
[0224] The specification of the obtained fast moisture-conducting fiber is 20D / 24F; the monofilament of the fast moisture-conducting fiber has a convex rough surface, with one convexity every 0.5-2 μm, and the average distance between adjacent convexities is 0.9 μm;
[0225] (5) Preparation of fabrics with rapid moisture conduction;
[0226] Firstly, the fast moisture-conducting fiber is spun to obtain the fast moisture-conducting yarn, and then the fast moisture-conducting yarn is woven into the fast moisture-conducting fabric.
[0227] The final fast moisture-conducting fabric is a woven plain fabric with a warp density of 120 strands / 10cm, a weft density of 130 strands / 10cm, and a gram weight of 40g / m 2 The water absorption rate of the fast-wicking fabric is 166%, the water droplet diffusion time is 1.2s, the wicking height is 121mm, and the drying rate is 0.59g / h.
[0228] Example B4
[0229] A method for preparing a fabric with rapid moisture conduction, the specific steps are as follows:
[0230] (1) Preparation of raw materials;
[0231] Coupling agent: N-(β-aminoethyl)-γ-aminopropyltrimethyl(ethyl)oxysilane;
[0232] Functional particles: zinc oxide;
[0233] Dibasic acid: pimelic acid;
[0234] Diamine: ethylenediamine;
[0235] Deionized water;
[0236] Catalyst: tetrabutyl titanate;
[0237] Resin A and Resin B: both are polyamides with an average degree of polymerization of 200;
[0238] NaOH aqueous solution: temperature 93°C, concentration 140g / L;
[0239] (2) Preparation of coated modified functional particles;
[0240] (2.1) In a high-speed blender, at a speed of 3000 r / min and a temperature of 100° C., the functional particles are subjected to organic modification using a coupling agent for 2 h to obtain coupling agent-modified functional particles; wherein the mass of the coupling agent is 3.5% of the mass of the functional particles;
[0241] (2.2) Add a dibasic acid, a diamine, and deionized water into a reactor, replace the air in the reactor with nitrogen or an inert gas (i.e., introduce 0.4 MPa of nitrogen or an inert gas into the reactor, open the exhaust valve to discharge, and repeat 3 times), react at 250°C and 1.6 MPa for 3 hours, then reduce the pressure to 0.1 MPa, add a catalyst, raise the temperature to 260°C, and turn on the vacuum pump to maintain the vacuum degree at 70 Pa, react for 3 hours, then raise the pressure to 0.1 MPa, and reduce the temperature to 220°C to obtain a polyamide oligomer with an average degree of polymerization of 30; wherein the molar ratio of the dibasic acid to the diamine is 1:0.95, the molar ratio of deionized water to the dibasic acid is 0.38:1, and the mass of the catalyst is 0.1% of the mass of the dibasic acid;
[0242] (2.3) adding coupling agent modified functional particles to the reaction system of step (2.2), stirring to fully mix, keeping the temperature for reaction for 1 hour, continuously evacuating, discharging, cooling, pre-crushing, air flow crushing, and obtaining coated modified functional particles; wherein the mass ratio of coupling agent modified functional particles to polyester oligomer is 8:1;
[0243] The prepared coated modified functional particles consist of functional particles and polyamide oligomers coated on the surface thereof, and the functional particles and the polyamide oligomers are covalently bonded via a coupling agent; the D50 particle size of the coated modified functional particles is 200 nm, and the thickness of the polyamide oligomers on the surface of the functional particles is 50 nm;
[0244] (3) preparing a spinning melt;
[0245] First, resin A and coated modified functional particles are melt-blended to obtain a masterbatch with a concentration of 65wt%, and then the masterbatch is melt-blended with resin B to obtain a spinning melt;
[0246] In the spinning melt, the content of the coated modified functional particles is 15wt%;
[0247] (4) Preparation of fibers that conduct moisture quickly;
[0248] First, the spinning melt is spun according to the POY process to obtain POY fibers, and then the POY fibers are soaked in a NaOH aqueous solution for 1.5 minutes, washed, and dried, and then the POY fibers are drawn using four pairs of drawing rollers to obtain fibers with rapid moisture conduction;
[0249] Among them, the temperature of the first pair of drafting rollers is 110°C, the temperature of the second pair of drafting rollers is 145°C, the temperature of the third pair of drafting rollers is 195°C, and the temperature of the fourth pair of drafting rollers is 230°C; the spinning speed of the first pair of drafting rollers is 450m / min, the spinning speed of the second pair of drafting rollers is 1200m / min, the spinning speed of the third pair of drafting rollers is 2400m / min, and the spinning speed of the fourth pair of drafting rollers is 2650m / min;
[0250] The specification of the obtained fast moisture-conducting fiber is 75D / 36F; the monofilament of the fast moisture-conducting fiber has a convex rough surface, with one convexity every 0.5-2 μm, and the average distance between adjacent convexities is 1.6 μm;
[0251] (5) Preparation of fabrics with rapid moisture conduction;
[0252] Firstly, the fast moisture-conducting fiber is spun to obtain the fast moisture-conducting yarn, and then the fast moisture-conducting yarn is woven into the fast moisture-conducting fabric.
[0253] The final fast moisture-wicking fabric is a knitted fabric with a circular knitting machine needle count of 40G and a gram weight of 200g / m 2 The water absorption rate of the fast-wicking fabric is 175%, the water droplet diffusion time is 1.4s, the wicking height is 118mm, and the drying rate is 0.53g / h.
[0254] Example B5
[0255] A method for preparing a fabric with rapid moisture conduction, the specific steps are as follows:
[0256] (1) Preparation of raw materials;
[0257] Coupling agent: isopropyl triisostearate titanate;
[0258] Functional particles: silicon dioxide;
[0259] Dibasic acid: suberic acid;
[0260] Diamine: pentamethylenediamine;
[0261] Deionized water;
[0262] Catalyst: tetrabutyl titanate;
[0263] Resin A and Resin B: both are polyamides with an average degree of polymerization of 150;
[0264] NaOH aqueous solution: temperature 95°C, concentration 170g / L;
[0265] (2) Preparation of coated modified functional particles;
[0266] (2.1) In a high-speed blender, at a speed of 2500 r / min and a temperature of 90°C, the functional particles are subjected to organic modification using a coupling agent for 3 hours to obtain coupling agent-modified functional particles; wherein the mass of the coupling agent is 4.5% of the mass of the functional particles;
[0267] (2.2) Add dibasic acid, diamine and deionized water into a reactor, replace the air in the reactor with nitrogen or inert gas (i.e., introduce 0.6 MPa of nitrogen or inert gas into the reactor, open the exhaust valve to discharge, and repeat 3 times), react at 250°C and 1.8 MPa for 3 hours, then reduce the pressure to 0.1 MPa, add catalyst, increase the temperature to 260°C, turn on the vacuum pump, maintain the vacuum degree at 72 Pa, react for 3 hours, then increase the pressure to 0.1 MPa, and reduce the temperature to 220°C to obtain a polyamide oligomer with an average degree of polymerization of 26; wherein the molar ratio of dibasic acid to diamine is 1:0.95, the molar ratio of deionized water to dibasic acid is 0.4:1, and the mass of the catalyst is 0.1% of the mass of the dibasic acid;
[0268] (2.3) adding coupling agent modified functional particles to the reaction system of step (2.2), stirring to fully mix, keeping the temperature for reaction for 1 hour, continuously evacuating, discharging, cooling, pre-crushing, air flow crushing, and obtaining coated modified functional particles; wherein the mass ratio of coupling agent modified functional particles to polyester oligomer is 7:1;
[0269] The prepared coated modified functional particles consist of functional particles and polyamide oligomers coated on the surface thereof, and the functional particles and the polyamide oligomers are covalently bonded via a coupling agent; the D50 particle size of the coated modified functional particles is 600 nm, and the thickness of the polyamide oligomers on the surface of the functional particles is 80 nm;
[0270] (3) preparing a spinning melt;
[0271] First, the resin A and the coated modified functional particles are melt-blended to obtain a masterbatch with a concentration of 50wt%, and then the masterbatch is melt-blended with the resin B to obtain a spinning melt;
[0272] In the spinning melt, the content of the coated modified functional particles is 15wt%;
[0273] (4) Preparation of fibers that conduct moisture quickly;
[0274] First, the spinning melt is spun according to the POY process to obtain POY fibers, and then the POY fibers are soaked in a NaOH aqueous solution for 1.5 minutes, washed, and dried, and then the POY fibers are drawn using four pairs of drawing rollers to obtain fibers with rapid moisture conduction;
[0275] Among them, the temperature of the first pair of drafting rollers is 105°C, the temperature of the second pair of drafting rollers is 135°C, the temperature of the third pair of drafting rollers is 190°C, and the temperature of the fourth pair of drafting rollers is 225°C; the spinning speed of the first pair of drafting rollers is 500m / min, the spinning speed of the second pair of drafting rollers is 1500m / min, the spinning speed of the third pair of drafting rollers is 2600m / min, and the spinning speed of the fourth pair of drafting rollers is 2800m / min;
[0276] The specification of the obtained fast moisture-conducting fiber is 150D / 72F; the monofilament of the fast moisture-conducting fiber has a convex rough surface, with one convexity every 0.5-2 μm, and the average distance between adjacent convexities is 1.8 μm;
[0277] (5) Preparation of fabrics with rapid moisture conduction;
[0278] Firstly, the fast moisture-conducting fiber is spun to obtain the fast moisture-conducting yarn, and then the fast moisture-conducting yarn is woven into the fast moisture-conducting fabric.
[0279] The final fast moisture-wicking fabric is a woven twill fabric with a warp density of 130 strands / 10cm, a weft density of 140 strands / 10cm, and a gram weight of 160g / m 2 The water absorption rate of the fast-wicking fabric is 163%, the water droplet diffusion time is 1.6s, the wicking height is 116mm, and the drying rate is 0.47g / h.
Claims
1. A method for preparing a fiber with rapid moisture conduction, characterized in that: The spinning melt containing 8-15 wt% of the coated modified functional particles is spun, and the spun melt is drafted 5.5-6.5 times during the spinning process to obtain a fiber with rapid moisture conduction; The D50 particle size of the coated modified functional particles is 50~900nm; The coated modified functional particles include functional particles and oligomers coated on the surface of the functional particles through covalent bonds. The oligomers and the matrix of the spinning melt are only different in average polymerization degree, and the average polymerization degree of the oligomers is 20-60.
2. The method for preparing a fast moisture-conducting fiber according to claim 1, characterized in that: The functional particles are silicon dioxide, titanium dioxide, zinc oxide, cuprous oxide or aluminum oxide; the thickness of the oligomers on the surface of the functional particles is 10-100 nm.
3. The method for preparing a fast moisture-conducting fiber according to claim 2, characterized in that: The preparation method of the coated modified functional particles is: firstly, a coupling agent is used to organically modify the functional particles to obtain coupling agent modified functional particles, and oligomers are prepared at the same time, and then the oligomers and the coupling agent modified functional particles are mixed and reacted.
4. The method for preparing a fast moisture-conducting fiber according to claim 3, characterized in that: The coupling agent is one or more of γ-aminopropyltriethoxysilane, γ-(2,3-epoxypropoxy)propyltrimethoxysilane, γ-methacryloxypropyltrimethoxysilane, N-(β-aminoethyl)-γ-aminopropyltrimethoxy(ethyl)silane, n-octyltriethoxysilane, vinyltriethoxysilane, isopropyltriisostearate titanate, isopropoxytri(dioctylpyrophosphate)titanate, tridecafluorooctyltrimethoxysilane, and perfluorodecyltrimethoxysilane; the mass of the coupling agent is 3-5% of the mass of the functional particles; the organic modification is completed in a high-speed blender at a speed of 2500-3000 r / min, a temperature of 80-100°C, and a time of 2-3h.
5. The method for preparing a fast moisture-conducting fiber according to claim 2, characterized in that: The oligomer is a polyester oligomer, the matrix of the spinning melt is polyester, and the preparation steps of the coated modified functional particles are as follows: (a) using a coupling agent to organically modify the functional particles to obtain coupling agent-modified functional particles; (b) adding the dibasic acid and diol into a reaction kettle, stirring and heating to 200-230°C, controlling the pressure of the reaction system to be 0.2-0.3MPa, adding a catalyst after reacting for 3-5h, controlling the temperature of the reaction system to gradually rise to 260-270°C, evacuating to a vacuum degree of less than 80Pa, reacting for 2-3h, cooling to 230°C, and obtaining an oligomer; (c) adding the coupling agent modified functional particles to the reaction system of step (b), stirring to fully mix, keeping the temperature for reaction for 0.5 to 1 hour, continuously evacuating, discharging, cooling, pre-crushing, and airflow crushing to obtain coated modified functional particles; The dibasic acid is terephthalic acid; the diol is one or more of ethylene glycol, propylene glycol and butanediol.
6. The method for preparing a fast moisture-conducting fiber according to claim 5, characterized in that: The molar ratio of the dibasic acid to the diol is 1:0.9-0.95; the mass of the catalyst is 0.01-0.1% of the mass of the dibasic acid; and the mass ratio of the coupling agent modified functional particles to the oligomer is 5-8:
1.
7. The method for preparing a fast moisture-conducting fiber according to claim 2, characterized in that: The oligomer is a polyamide oligomer, the matrix of the spinning melt is polyamide, and the preparation steps of the coated modified functional particles are as follows: (I) using a coupling agent to organically modify the functional particles to obtain coupling agent-modified functional particles; (II) Add dibasic acid, diamine and deionized water into a reactor, replace the air in the reactor with nitrogen or inert gas, react at 250°C and 1.3-1.8MPa for 3h, then reduce the pressure to 0.1MPa, add a catalyst, increase the temperature to 260°C, turn on the vacuum pump, keep the vacuum degree below 80Pa, react for 2-3h, then increase the pressure to 0.1MPa, and reduce the temperature to 220°C to obtain an oligomer; (III) adding the coupling agent modified functional particles to the reaction system of step (II), stirring to fully mix, keeping the temperature for reaction for 0.5 to 1 hour, continuously evacuating, discharging, cooling, pre-crushing, and airflow crushing to obtain coated modified functional particles; The dibasic acid is one or more of succinic acid, glutaric acid, adipic acid, pimelic acid, suberic acid, azelaic acid, and sebacic acid; the diamine is one or more of pentamethylenediamine and ethylenediamine.
8. The method for preparing a fast moisture-conducting fiber according to claim 7, characterized in that: The molar ratio of the dibasic acid to the diamine is 1:0.9-0.95; the molar ratio of deionized water to the dibasic acid is 0.3-0.4:1; the mass of the catalyst is 0.05-0.1% of the mass of the dibasic acid; and the mass ratio of the coupling agent modified functional particles to the oligomer is 5-8:
1.
9. The method for preparing a fast moisture-conducting fiber according to any one of claims 5 to 8, characterized in that: The preparation process of the spinning melt is: firstly melt-blending resin A and the coated modified functional particles to obtain a masterbatch with a concentration of 50-65wt%, and then melt-blending the masterbatch with resin B to obtain a spinning melt, wherein resin A and resin B are the same substance.
10. The method for preparing a fast moisture-conducting fiber according to claim 9, characterized in that: Four pairs of drafting rollers are used for drafting; the temperature of the first pair of drafting rollers is 100~120℃, the temperature of the second pair of drafting rollers is 130~150℃, the temperature of the third pair of drafting rollers is 180~200℃, and the temperature of the fourth pair of drafting rollers is 200~240℃; the spinning speed of the first pair of drafting rollers is 400~500m / min, the spinning speed of the second pair of drafting rollers is 1200~1500m / min, the spinning speed of the third pair of drafting rollers is 2400~2600m / min, and the spinning speed of the fourth pair of drafting rollers is 2600~2800m / min.
11. The method for preparing a fast moisture-conducting fiber according to claim 9, characterized in that: The spinning is directly carried out according to the FDY process, or the POY process is firstly carried out to obtain POY yarn, and then the POY yarn is alkali-etched, and then the POY yarn after alkali etching is drawn. The alkali etching treatment is to immerse the POY yarn in a NaOH aqueous solution with a temperature of 90-95° C. and a concentration of 120-170 g / L for 1-2 minutes, and then wash and dry.
12. A fast moisture-conducting fiber prepared by the method for preparing a fast moisture-conducting fiber according to any one of claims 1 to 11, characterized in that: The monofilament has a rough surface with protrusions, with one protrusion every 0.5~2μm.
13. A yarn with rapid moisture conduction, characterized in that: It is spun from the fast moisture-conducting fiber as described in claim 12.
14. A fast moisture-wicking fabric, characterized in that: It is woven from the fast moisture-conducting yarn as described in claim 13.
15. A fast moisture-wicking fabric according to claim 14, characterized in that: The fabric that conducts moisture quickly is a knitted fabric, the needle count of the circular knitting machine is 40G, and the weight is 150~300g / m 2 Or, the fabric for rapid moisture conduction is a woven plain fabric with a warp density of 120-130 strands / 10cm, a weft density of 130-150 strands / 10cm, and a gram weight of 40-300g / m 2 Or, the fast moisture-wicking fabric is a woven twill fabric with a warp density of 120-190 strands / 10cm, a weft density of 140-150 strands / 10cm, and a gram weight of 60-300g / m 2 ; The water absorption rate of the fast moisture-conducting fabric is ≥152%, the water droplet diffusion time is ≤1.9s, the wicking height is ≥112mm, and the drying rate is ≥0.45g / h.
Citation Information
Patent Citations
Knitted fabric based on modified polyamide fiber material and preparation method thereof
CN118186671A
Processing technology of quick-dry antibacterial cotton fiber blended fabric
CN118308830A
Moisture-absorbing and quick-drying fabric
CN118345551A
Warp-knitted double-sided fluff fabric with moisture absorption and quick drying functions and preparation method of warp-knitted double-sided fluff fabric
CN118360722A
Multi-groove profiled fiber and preparation method of fabric of multi-groove profiled fiber
CN118407153A